2010
DOI: 10.3139/113.110078
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Polyglycoside-Sorbitan Ester Formulations for Improved Oil Recovery

Abstract: We measured interfacial tensions (IFT) of aqueous alkyl polyglucoside (APG) systems formulated with sorbitan ester-type cosurfactants against n-octane. The study focused on low to ultralow IFT systems which are relevant for enhanced oil recovery (EOR). In addition, we measured equilibrium adsorption concentrations of these surfactants and cosurfactants onto kaolinite clay, commonly found in oil reservoirs. We present one surfactant EOR laboratory flood experiment with one selected APGsorbitan ester formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In addition, the high lutein extraction efficiency of synthetic surfactants compared to their natural counterparts at SOR max (Tables 1 and 2) may also be connected with their CMCs. For instance, a relationship can be seen between the high efficiency of T80 (39.41%) and S20 (35.67%) with their low CMCs (0.017 and 0.024 mM L −1 ) consequently high C max 2/CMC ratios (710.82 and 953.16), respectively [30, 31]. It is reported that at high concentrations, slightly higher than CMC, the micelles usually aggregate or even coalesce [32].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high lutein extraction efficiency of synthetic surfactants compared to their natural counterparts at SOR max (Tables 1 and 2) may also be connected with their CMCs. For instance, a relationship can be seen between the high efficiency of T80 (39.41%) and S20 (35.67%) with their low CMCs (0.017 and 0.024 mM L −1 ) consequently high C max 2/CMC ratios (710.82 and 953.16), respectively [30, 31]. It is reported that at high concentrations, slightly higher than CMC, the micelles usually aggregate or even coalesce [32].…”
Section: Resultsmentioning
confidence: 99%
“…70°C while mixing (Wu et al . ). The solutions of sorbitan monostearate stayed dispersed for the duration of the experiment ( c .…”
Section: Methodsmentioning
confidence: 97%
“…Surfactants were added to the water, covered, then mixed for 5 min. Sorbitan monostearate was not miscible in room temperature water, and was dispersed by warming the water to c. 70°C while mixing (Wu et al 2010). The solutions of sorbitan monostearate stayed dispersed for the duration of the experiment (c. 1 h).…”
Section: Surfactantmentioning
confidence: 99%
“…Tatsumi et al have reported the use of cationic gemini surfactants with two quaternary ammonium groups in the polar head and two hydrolysable amide groups in the lipophilic portions [17]. Hydrophilic nature of spacer contributes to the higher water solubility that helps in hydrolysis and degradation processes [17][18][19][20][21]. Cationic surfactants have been successfully employed to interact with the negatively charged surfaces or biomolecules such as prokaryotic/eukaryotic cells, antigenic proteins, lipids, etc.…”
Section: Page 6 Of 29mentioning
confidence: 99%